Exploring the ESP Students' Voices on the Integrated English Skills for Professional Context - Rozanah Katrina Herda; Bonifasia Ekta Fima Natalia; Zohaib Hassan Sain (Universitas Muria Kudus, 2025)
In today’s globalized world, proficiency in English has become a vital skill for students pursuing careers in various professional fields. For accounting students, mastering integrated English skills is essential for success in their academic and professional endeavours. This study explores students' perceptions of the importance of integrated English skills for professional contexts and examines how these skills impact their academic performance and success. The participants were 47 undergraduate students from non-English departments, majoring in Accounting. The combination of quantitative and qualitative approaches allows for a comprehensive understanding of the students’ perspectives by distributing questionnaires and conducting semi-structured interviews. The findings showed that students perceive proficiency in all four language skills as essential for their future professional contexts, particularly in the accounting field. This study highlights several advantages of mastering integrated English skills for accounting students, emphasizing the practical benefits these skills bring to their academic and professional lives. Furthermore, by focusing on their perspectives, this study contributes to a more inclusive understanding of how integrated English skills are developed and utilized in real-world professional settings.